KERAGAMAN KONSUMSI PANGAN SEBAGAI FAKTOR RISIKO STUNTING PADA BALITA USIA 6-24 BULAN - Mira Wantina; Leni Sri Rahayu; Indah Yuliana (ARGIPA (Arsip Gizi dan Pangan), 2017)
Stunting is a problem of chronic undernourishment caused by the intake of nutrientsquality and food diversity. The purpose of this research is to know the relationship diversityof food consumption with stunting on toddler age 6-24 months. The methodology used isdescriptive qualitative approach. The design in this study was a crosssectional study. Thesample in this research totalled 82 toddlers aged 6-24 months. Data collection was conductedin the village of Cimayang. Data analysis technique used was chi square. The results showedthere was a relationship between parenting, complementary feeding breast milk, hygiene andsanitation practices, and the diversity of food consumption with stunting on toddler age 6-24months (p-value 0.015). The more food consumption diversity, will be the better quality ofnutrition value. Education about the diversity of food consumption is needed, especially tomothers with toddlers.